Gut Microbiota and Type 1 Diabetes Mellitus: The Effect of Mediterranean Diet - Calabrese, Cinzia Myriam; Valentini, Alessia; Calabrese, Giorgio (Frontiers in Nutrition, 2021)
Type 1 diabetes mellitus (T1DM) is a chronic autoimmune disease resulting from a complex interplay between genetic susceptibility and environmental factors. Regarding the latter, gut microbiota has a pivotal role in the pathogenesis of T1DM, by affecting intestinal permeability, molecular mimicry, and modulating innate and adaptive immune system, as described in several previous studies. The composition of the gut microbiota is largely influenced by diet. Some observational studies have shown that a low fiber intake is associated to the development of many inflammatory and immune-mediated diseases. In this context, the Mediterranean Diet (MD), which is based on high consumption of cereals (preferably as whole grains), legumes, nuts, vegetables, fruits, olive oil, and fish, could play a protective role. Many of the characteristic components of MD have functional characteristics with positive effects on health and well-being. Eating habits are the main significant determinants of the microbial multiplicity of the intestine and the food components influence both microbial populations and their metabolic activities from the early stages of life. Moreover, food metabolites influence the immune response. The intestine is considered the primary site where food metabolites mediate their effects, through epithelial integrity or mucosal immunity. The compromised epithelial integrity allows the translocation of bacteria and/or the diffusion of their products, such as food antigens and lipopolysaccharides, from the intestinal lumen to the tissues, which could enhance the stimulation of immune cells, contributing to the pathogenesis of autoimmune diseases, such as T1DM. The intake of a high amount of fiber and therefore of prebiotics with MD allows the microbiota to have a good microbial balance. Moreover, as more dietary fibers are ingested, a higher amount of short-chain fatty acids (SCFAs) is produced by anaerobic gut microbiota, promoting gut homeostasis, to which also contribute tryptophan metabolites and omega-3-fatty acids. Furthermore, the higher intake of polyunsaturated fatty acids and omega-3-fatty-acids contribute to a better metabolic control. In this review we report the relationship between gut microbiota and T1DM and we explore the effects of Mediterranean Diet on microbiota as a potential therapeutic strategy, aimed at preventing or delaying progression of T1DM and its complications.